MMP-9 Inhibition Suppresses Interferon-γ-Induced CXCL10 Production in Human Salivary Gland Ductal Cells - Aota, Keiko; Ono, Shinji; Yamanoi, Tomoko; Kani, Koichi; Momota, Yukihiro; Azuma, Masayuki (Inflammation, 2019)
Gene expression profiling of lip salivary gland (LSG) has shown that C-X-C motif chemokine 10 ( CXCL10 ) and matrix metalloproteinase 9 ( MMP9 ) expression is upregulated in primary Sjögren’s syndrome (pSS) patients. Although CXCL10 and MMP-9 are both associated with pSS pathogenesis, the potential relationship between these two factors has not been investigated. In this study, we used LSG sections from pSS patients and human salivary gland cell lines to investigate the relationship between CXCL10 and MMP-9. Immunofluorescence analyses revealed that CXCL10 and MMP-9 were co-expressed in the LSG of pSS patients, particularly in expanded ductal cells. Furthermore, RT-qPCR analyses on human salivary gland ductal NS-SV-DC cells confirmed that CXCL10 expression was induced by interferon (IFN)-γ, whereas that of MMP9 was stimulated by IFN-α, tumor necrosis factor-α, and interleukin-1β. Remarkably, MMP-9 inhibition in IFN-γ-stimulated NS-SV-DC cells significantly decreased CXCL10 mRNA and secreted protein levels. Further analyses established that MMP-9 inhibition in IFN-γ-stimulated NS-SV-DC cells decreased STAT1 phosphorylation and hence suppressed IFN-γ signaling. Collectively, these results suggest that in addition to its reported role in the destruction of acinar structures, MMP-9 is involved in the IFN-γ-induced production of CXCL10 in pSS lesions. We believe that our findings open the door to the development of novel treatments for pSS, based on the modulation of MMP-9 activity.